Interannual variability of nonlinear internal wave characteristics in the Pacific Ocean off the Kamchatka Peninsula and the Northern Kuril Islands - Zimin, Alexey; Svergun, Egor; Sofina, Ekaterina; Romanenkov, Dmitry; Varkentin, Aleksandr; Konik, Aleksandr; Atadzhanova, Oksana; Makhovikov, Aleksei; Vinogradova, Irina (Frontiers in Marine Science, 2025)
In the North Pacific Ocean off the Kamchatka Peninsula, nonlinear internal waves (NLIWs) are still studied insufficiently. The purpose of the study was to establish patterns in the distribution of NLIW characteristics and the reasons for their significant variability. The study used Sentinel-1 radar images from 2015 to 2024, along with data from the FESOM-C tidal model, Landsat 8, Sentinel-2, and estimates of Kamchatka walleye pollock population. In total, 3,895 NLIW events were identified, revealing “hot spots” with high wave activity, mainly east of the Fourth Kuril Strait, on Kamchatka’s shelf, and around the Shipunsky Peninsula. NLIW characteristics obtained from satellite observations were supplemented by in-situ measurement near the Shipunsky Peninsula. NLIWs peaked in summer and were least active in winter. The maximum occurrence within а year was linked to the strong subsurface pycnocline, intensified tidal currents, and weak winds. “Hot spots” coincided with areas of strong diurnal tidal currents, suggesting that topographically trapped diurnal internal tide generates many NLIWs. Results also demonstrate NLIW influence on chlorophyll-a distribution and their potential role in supporting feeding base of juvenile walleye pollock, indicating the importance of internal waves in shaping the local ecosystem.